Obstructive Sleep Apnea Syndrome and the correlation with obesity - Souza, Alesandra Perazzoli de; Santos, Paola Ribas Gonçalves dos; Cachoeira, Flavia Eduarda; Martinello, Micheli; Ribeiro, Maykon (Seven Editora, 2023)
Introduction: Sleep apnea is a chronic, disabling disorder that has alarming consequences, since its pathophysiological mechanism implies changes in respiratory control. It consists of partial or total obstruction of the upper airways resulting in reduction or interruption of oxygen flow for 10 seconds, interrupting sleep. Method: Bibliographic review study in the databases Scielo, Virtual Health Library (VHL) and Google Scholar published from 2008 to April 2021, in Portuguese and English being randomized clinical trials, excluding other types of studies. Results: After the selection of the articles, based on the inclusion and exclusion criteria, 16 articles were included for the elaboration of the analysis and the abstract. Obstruction of the upper airways in obese patients occurs by excess adipose tissue, which accumulates in some organs and makes the respiratory system narrower, aggravating its manifestation. The coexistence of Obstructive Sleep Apnea Syndrome with obesity exacerbates the risk factors and secondary complications for the development of other comorbidities such as hypertension and heart failure, as well as hormonal imbalance, increasing the plasma levels of ghrelin that predisposes the development of Diabetes Melittus type 2. Conclusions: It is essential to apply therapeutic measures aimed at reducing upper airway obstruction, as well as its collapse, and it is necessary to associate the treatment to reduce obesity in order to improve pulmonary ventilation-perfusion of patients with these pathologies. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-003